HRM-Based Service Quality and Marketing Strategy on Passenger Travel Experience during Eid Peak Season - Ratih Ikha Permata; Abdul Samad Latuconsina; Sumardi Sumardi; Ansir Lautu; Subehana Rachman (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study analyzes the influence of Human Resource Management (HRM)–based service quality and marketing strategies on passenger travel experience during the Eid peak season, both partially and simultaneously.Research Methodology: This study employs a quantitative survey of airline passengers traveling during the Eid peak season. Convenience sampling was applied through an online questionnaire distributed via Google Forms, involving 150 respondents based on the predetermined minimum sample criteria. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0.Results: Human Resource Based Service Quality (HRSQ) positively affected passenger travel experience (? = 0.233, p = 0.017), while marketing strategy showed a stronger positive effect (? = 0.523, p < 0.001). Both variables explained 46.9% of the variance in passenger travel experience (R² = 0.469). These findings indicate that enhancing service quality through human resource capabilities and effective marketing strategies is essential for improving passengers’ overall travel experiences.Conclusions: Airlines should enhance service quality through continuous staff training and innovative marketing strategies to improve passenger travel experience during the Eid peak season.Limitations: The convenience sample, dominated by students, limits generalizability, and discriminant validity and common method bias were not fully tested.Contributions: This study provides empirical evidence from Indonesia aviation industry during the underexplored Eid peak season and offers practical guidance for improving passenger experience under peak operational conditions.